Developmental Processes in Networked Learning: Orientation - Levy, Philippa (Proceedings of the International Conference on Networked Learning, 2004)
This paper reports some of the findings of practice-based, case study evaluation research that examined participants’ experiences of a networked learning approach to professional development. The research revealed networked learners’ experiences of four broad, interconnected developmental processes - orientation, socialisation, communication and organization - and the impact of these on the nature and quality of engagement with the learning environment and tasks. The paper focuses on experiences of orientation, concluding by highlighting some practical evaluation implications arising out of this research, and by suggesting that it points to more general considerations for networked learning design and facilitation.